Exposure to an Indoor Cooking Fire and Risk of Trachoma in Children of Kongwa, Tanzania. - Andrea I Zambrano; Beatriz E Muñoz; Harran Mkocha; Sheila K West (Public Library of Science (PLoS), 2015)
BACKGROUND:Elimination of blinding trachoma by 2020 can only be achieved if affected areas have effective control programs in place before the target date. Identifying risk factors for active disease that are amenable to intervention is important to successfully design such programs. Previous studies have linked sleeping by a cooking fire to trachoma in children, but not fully explored the mechanism and risks. We propose to determine the risk for active trachoma in children with exposure to cooking fires by severity of trachoma, adjusting for other known risk factors. METHODS:Complete census of 52 communities in Kongwa, Tanzania, was conducted to collect basic household characteristics and demographic information on each family member. Information on exposure to indoor cooking fires while the mother was cooking and while sleeping for each child was collected. 6656 randomly selected children ages 1-9 yrs were invited to a survey where both eyelids were graded for follicular (TF) and intense trachoma (TI) using the WHO simplified grading scheme. Ocular swab were taken to assess the presence of Chlamydia trachomatis. FINDINGS:5240 (79%) of the invited children participated in the study. Overall prevalence for trachoma was 6·1%. Odds for trachoma and increased severity were higher in children sleeping without ventilation and a cooking fire in their room (TF OR = 1·81, 1·00-3·27 and TI OR 4·06, 1·96-8·42). Children with TF or TI who were exposed were more likely to have infection than children with TF or TI who were not exposed. There was no increased risk with exposure to a cooking fire while the mother was cooking. CONCLUSIONS:In addition to known risk factors for trachoma, sleeping by an indoor cooking fire in a room without ventilation was associated with active trachoma and appears to substantially increase the risk of intense inflammation.